TELECOMMUNICATION AND TECHNOLOGY: THE ROLE OF ICT COMPANIES IN MALAYSIA - Johar,; MGM,; Yajid, Mohd Shukri Ab (International Journal of Psychosocial Rehabilitation, 2020)
In the global world plenty of companies admit that telecommunication is the prominent source which must be arranged with same focus and loyalty as many other major expense areas such human, material, and financial. It is also being difficult as per the nature of industry with new emerging technologies, features and services rapidly. In order to enumerate and determine the adaptation of telecommunication technology, particularly VoIP service by ICT companies in Malaysia, qualitative and quantitative results are to be provided in accordance to the set of extensive questionnaire developed. Approximately 80 employees of working class from ICT companies were targeted at the main cities in Malaysia while the collection of data in this study, where different modeling techniques have been applied in this study. From the evolution of telecommunication technology, significant impact caused of especially the emergence of VoIP service, while an apparent positive response have been indicated towards the adaptation of new telecommunication technology by ICT companies in Malaysia.